Diagnostic performance of breast imaging with ultrasonography, magnetic resonance and mammography in the assessment of residual tumor after neoadjuvant chemotherapy in breast cancer patients - Yıldırım, Emine; Uçar, Neşe; Yetiş, Fırat; Kayadibi, Yasemin; Bektaş, Sibel (Journal of Surgery and Medicine, 2022)
Background/Aim: Following the administration of neoadjuvant chemotherapy (NAC), a complete pathological response (pCR) is seen at rates of up to 50-70% in breast cancer patients, especially in triple-negative (TNBC) and HER-2 enriched subgroups and related to increased pCR rates, studies to predict the pathological response with preoperative evaluation are ongoing. The aim of this study was to investigate the correlation of preoperative imaging in breast cancer patients receiving NAC with the pathological response. Methods: The study, organized as a retrospective cohort study, included 129 breast patients who underwent surgery after NAC between April 2014 and February 2020. The demographic data of the patients, the clinical and radiological findings before and after NAC, operation findings, and the histopathological evaluation results were collected retrospectively from the patient files. The radiological images of the patients were examined by separating into groups of patients with ultrasonography (US), magnetic resonance imaging (MRI), US+MRI, and mammography (MG)+US. The NAC response on preoperative breast US and MG was evaluated according to the RECIST-1.1 system, and the NAC response on MRI with the Goorts et al grading system. In the histopathological examination of operation material, the Miller Payne grading system for breast tissue was used in the determination of NAC response. Results: The mean age of the patients in the study was 49.17 (11.00) years. The vast majority of the patients (87.6%) were diagnosed with invasive ductal cancer, with 27.13% in luminal A, 35.65% in luminal B, 31.0% in HER-2 enriched, and 6.2% in TNBC subgroups. A statistically significant correlation was determined between the pathological response and the US+MRI, MRI, and US+MG groups, with agreement at a moderate level (Kappa: 0.653, P<0.001; Kappa:0.443, P<0.001; Kappa:0.481, P=0.005, respectively). Within all the groups, the group with the highest sensitivity and accuracy were seen to be the patients evaluated with US+MRI (66.67%, 90.91%, respectively). Conclusion: The results of this study demonstrated that there is a correlation between the pathological response and US+MRI, MRI, and US+MG evaluation after NAC. The US+MRI group was found to have the highest sensitivity, specificity, positive predictive value, negative predictive value, and accuracy. When possible, the use of these two imaging methods together in the preoperative evaluation of patients is a successful method in the prediction of pathological response.